Mucosal-associated invariant T cells in infectious diseases of respiratory system: recent advancements and applications - Xue Lin; Ye Wang; Yanqi He (BMC, 2024)
Abstract Mucosal-associated invariant T (MAIT) cells are an atypical subset of T lymphocytes, which have a highly conserved semi-constant αβ chain of T-cell receptor (TCR) and recognize microbe-derived vitamin B metabolites via major histocompatibility complex class I related-1 molecule (MR1). MAIT cells get activated mainly through unique TCR-dependent and TCR-independent pathways, and express multiple functional and phenotypic traits, including innate-like functionality, T helper (Th) 1 cell immunity, Th 17 cell immunity, and tissue homing. Given the functions, MAIT cells are extensively reported to play a key role in mucosal homeostasis and infectious diseases. In the current work, we review the basic characteristics of MAIT cells and their roles in mucosal homeostasis and development of respiratory infectious diseases as well as their potential therapeutic targets.